EPISTOMOLOGI HERMENEUTIKA HADIS FAZLUR RAHMAN: REFLEKSI TERHADAP KAJIAN PENDEKATA HADIS - Muhazir muhazir (At-Tafkir, 2016)
Studies on hermeneutics tradition has developed very rapidly. Onthe way, many approaches made by some Muslim intellectuals toget the real message of the hadith. Depth study of hadith is notonly perpetrated by the Muslim intellectuals, even orentalismegroups participating in the assessment of the tradition with adifferent purpose. Studies of Hadith orentalis much studied bypeople in a variety of disciplines, they are trying to put forwardnew theories in order analysis hadits. They think is Prophetictraditions that have experienced the purity of the text forintervention after the prophet's death.